Family Economy and Capitalist Subordination in Three Peasant Communities of Junín - Sánchez Enríquez, Rodrigo (1983)
In this work we want to draw attention to the different mechanisms by which the capitalist system manages to subordinate the family peasant economy to its accumulation circuits. With this we want to support the idea that, in the absence of a clear proletarianization, capitalism has no problem adapting to the maintenance and permanence of typically non-wage forms of production such as the family form.